O Bairro do Jardim Alvorada em Maringá/PR : da colonização à expansão urbana - Mansano, Cleres do Nascimento (2013)
The rapid expansion of Maringá urban area in Paraná, which was based on the logic estate agency, has marked its space since the beginning of the colonization conducted by the CTNP/CMNP. Conceived as a planned city in the 1940s, its neighborhood grew up and occupied the rural area surrounding the newly created city beyond their initial planning, especially in the 1960s when "Jardim Alvorada" started to be formed by the subdivision of "Fazenda Santa Lina" in the urban area. Just after 60 years, Maringá has expanded its village characteristic to a regional centre city, nowadays with more than 350,000 inhabitants. In this movement, some neighborhood stood out as places that maintain its own autonomy in relation to downtown, because they develop some urban functions that allows them to provide facilities to residents and around it. This research was done at Jardim Alvorada (From fiscal Zone 24 and part of Zone 46), with the purpose of explaining the highlight of this neighborhood in the urbanization process which has gone through in Maringa´city. In the methodology, it was used bibliographic studies and in special some conclusions of the geographical scientist Pierre Monbeig, and also statistical and documentary research, collection and systematization of data, survey of iconographic material and it was conducted field studies among the population who uses the neighborhood, through interviews and questionnaires in some institutions that could provide information about the neighborhood. To develop the research it was treated the landscape, place and society concepts. It was possible to observe that the same current speculation process promoted by the estate agents in Maringa had been part of the process of colonization and expansion of the city. However, in the colonization municipality process, the mapped places have showed some peculiarities that turned them into a standing out neighborhood as well in the economic, political, social and cultural life in Maringá. You can also see some colonization resquices among the neighborhood which are in constant transformation. Although inserted in the colonization process which targeted the Northern of Paraná and Maringa, and part of it was the periphery of the city, Jardim Alvorada exceed "maringaense's cenario, reaching the current situation as an structured local to meet the neighborhood population. This one has become a business point of reference, although it has already some problems like for example, the lack of adequated urban infrastructure and also socioeconomic problems, which are considered common in many Brazil districts.